Pendidikan Karakter Ki Hadjar Dewantara dan Penguatannya di Sekolah - Mus S. Radjilun; Hi. Thalib Abas (Jurnal Ilmiah Wahana Pendidikan, 2023)
Religious character values, honesty, tolerance, discipline, hard work, creativity, mutual cooperation, and love for the motherland are important points in character education. Character education aims to enable students to understand character values and ethics in the family, community, and state customs and laws. Ki Hadjar Dewantara's educational trilogy as a character education instrument. Students are able to develop their character or character consistently in making decisions with a character approach amidst the problems of life in today's society. The strategies that need to be used in implementing character in educational units are socialization, exemplary, habituation, development of regulations, capacity building, implementation and cooperation, monitoring and evaluation. The formation of student character education in schools is important for preparing future generations who are good and have strong character to face every changing era.